Evaluation of Renal Diseases using Isotope Renograme and Biochemical Test: a Correlative Study with 275 Cases (TAJ: Journal of Teachers Association, 2009)
The study was carried out with an aim to make a correlation between radionuclide renographyand biochemical test in the evaluation of renal diseases. A total of 275 patients with a history oflow back pain were included in the study. Radionuclide renography and biochemical test weredone in most of them in consecutive days. Among them, 241 patients were finally found to bepositive. Available USG, X-ray, IVU, TC, DC, ESR and Hb% findings were also correlated wellwith renogram. Renal diseases like renal stone, acute glomerulonephritis (AGN), ureteric stone,enal abscess, chronic renal failure, end stage renal disease (ESRD) and renal trauma wereound in most of the cases. In case of radionuclide renography, mild to severe renalnsufficiency found in 87.64% cases (single & bilateral) in contrast to biochemical test wherencreased blood urea/ serum creatinine found in 30.91% cases. Our study focuses themportance of renogram technique over biochemical test for precise evaluation of differentialrenal function.doi: 10.3329/taj.v16i2.3885TAJ December 2003; Vol.16(2): 65-67